The Pyramid of Queen Setibhor at South Saqqara - Megahed, Mohamed; Vymazalová, Hana (Études et Travaux, 2022)
This paper aims to present the preliminary results of the 2021 season of the Djedkare Project mission (DJP), which is dedicated to the exploration and documentation of Djedkare’s royal cemetery at south Saqqara. The main focus of the article is the queen’s pyramid, situated to the north-east of the king’s pyramid and to the north of his funerary temple. The 2018 exploration of the area between the king’s temple and the queen’s pyramid not only revealed the name of the owner, Setibhor, but it also confirmed that the two pyramid complexes were not architecturally connected, as previously presumed, and that further work is needed to clarify the plan of the queen’s monument. In 2021, the investigations focused on the pyramid of the queen; its substructure had never been entered and documented in the modern period. Cleaning the substructure resulted in a detailed documentation of its inner rooms. It used to be accessed through a descending and horizontal corridor and it comprised a burial chamber and a so-called serdab. The innovated layout of Setibhor’s pyramid substructure apparently inspired later queens, who continued to follow this pattern in their monuments during the Sixth Dynasty.